2022
DOI: 10.3390/biom12030439
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic L1 Adhesion Molecule Mimetic Compounds Inhibit Glioblastoma Cell Migration In Vitro

Abstract: Cell adhesion molecule L1 is a cell surface glycoprotein that promotes neuronal cell migration, fosters regeneration after spinal cord injury and ameliorates the consequences of neuronal degeneration in mouse and zebrafish models. Counter-indicative features of L1 were found in tumor progression: the more L1 is expressed, the more tumor cells migrate and increase their metastatic potential. L1′s metastatic potential is further evidenced by its promotion of epithelial–mesenchymal transition, endothelial cell tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 47 publications
(57 reference statements)
2
9
0
Order By: Relevance
“… 27 Antagonistic mimetic compounds targeting L1CAM decreases glioblastoma cell migration. 28 Specifically, increased L1CAM expression has been observed in LUSC patients and has a close correlation with an adverse prognosis in LUSC. Functional enrichment analysis showed that the upregulated genes correlated with L1CAM were primarily implicated in various tumor microenvironment remodeling and growth factor‐related pathway, including the EMT process, collagen formation and NRAS pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Antagonistic mimetic compounds targeting L1CAM decreases glioblastoma cell migration. 28 Specifically, increased L1CAM expression has been observed in LUSC patients and has a close correlation with an adverse prognosis in LUSC. Functional enrichment analysis showed that the upregulated genes correlated with L1CAM were primarily implicated in various tumor microenvironment remodeling and growth factor‐related pathway, including the EMT process, collagen formation and NRAS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…LUAD patients with high L1CAM expression in surgically‐resected brain metastases have been reported to have an unfavorable overall survival time 27 . Antagonistic mimetic compounds targeting L1CAM decreases glioblastoma cell migration 28 . Specifically, increased L1CAM expression has been observed in LUSC patients and has a close correlation with an adverse prognosis in LUSC.…”
Section: Discussionmentioning
confidence: 99%
“…Deforolimus decreases the mammalian target of rapamycin pathway activation and inhibits glioma growth in certain subtypes (Hütt-Cabezas et al, 2013). Anagrelide inhibits GBM cell migration in vitro in an L1-dependent manner (Nagaraj et al, 2022). Vemurafenib demonstrated durable antitumor activity in some patients with BRAF V600 -mutant gliomas (Kaley et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To identify mimetics of ED peptide, we screened small organic compounds as described [ 68 ] using the National Institute of Health Clinical Collection Libraries 1 and 2 (Evotec, Marburg, Germany) and the Natural Compound Library (Selleckchem, Houston, TX, USA) via competition ELISA. In brief, 384-well ELISA plates were coated with 1 µg/mL of antibody against ED.…”
Section: Methodsmentioning
confidence: 99%